PEMERIKSAAN KECACINGAN PADA ANAK-ANAK DI BEBERAPA PANTI ASUHAN KABUPATEN DAN KOTA JAYAPURA PAPUA (Jurnal Biogenerasi, 2024)
Helminth infections in children are generally caused by Soil Transmitted Helminth (STH) worm groups, namelyAscaris lumbricoides, Trichuris trichiura and hookworm. Children in orphanages who do not have parents and sometimes lack attention make them vulnerable to helminthiasis. This study was conducted in several orphanages, namely “A” Orphanage, “B” Orphanage Jayapura Regency, and “C” Orphanage Jayapura City, Papua. This study lasted for 3 months from November 5, 2022 - February 5, 2023. The purpose of this study was to determine the results of helminthiasis examination in children in the three orphanages. The type of research used was laboratory testing, the population in this study was feces from children in 90 orphanages, where each orphanage was sampled as many as 30 samples. The samples taken were examined using the direct method of 2% eosin as much as 2 drops. The results obtained showed that 30 samples from “A” Orphanage, 3 samples were positive for Trichiuris trichiura and Acaris lumbricoides worm eggs. Samples from “B”, 2 samples were positive for Trichiuris trichiura and Acaris lumbricoides worm eggs. While samples from “C” Orphanage Jayapura City, 2 samples were positive for eggs of Trichiuris trichiura and Acaris lumbricoides.
Keywords: Helminth Infection; Children; Orphanage